KEDUDUKAN JAMINAN ANTARA UTANG-PIUTANG DAN RAHN - Suwandi Suwandi (Fakultas Syariah, 2017)
The existence of a guarantee is a legal issue that needs to be explained in the problems of pawn. That was due to the shifting paradigm in the problem of pawn in terms of Islamic jurisprudence and economics are all boils down of debts.Position of assurance in debts should not exist. It is held when the element of trust doesn't exist. The position of guarantee on pawn must be existed and implemented before the contract of debts. The absence of collateral, debts not possibly be implemented.